2009
DOI: 10.1051/0004-6361/200810526
|View full text |Cite
|
Sign up to set email alerts
|

Properties and nature of Be stars

Abstract: Context. One way to understand the still mysterious Be phenomenon is to study the time variations of particular Be stars with a long observational history. ζ Tau is one obvious candidate. Aims. Using our rich series of spectral and photometric observations and a critical compilation of available radial velocities, spectrophotometry of Hα, and UBV photometry, we characterize the pattern of time variations of ζ Tau over about a century. Our goal is to find the true timescales of its variability and confront them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
(70 reference statements)
1
37
0
Order By: Relevance
“…Similar direct ultraviolet detections of hot subdwarf companions have been accomplished for FY CMa (Peters et al 2008), 59 Cyg (Peters et al 2013), HR 2142 (Peters et al 2016), and o Pup (Rivinius et al 2012, Koubský et al 2012) all with small mass functions in the range of 2 × 10 −3 − 1.3 × 10 −2 M ⊙ . Other Be binaries that have not had direct detections of the companion stars such as γ Cas (Smith et al 2012) or ζ Tau (Ruždjak et al 2009) also show similar mass functions (f (M ) = 1 × 10 −3 and f (M ) = 6 × 10 −3 respectively) that indicate low-mass companions. The mass function of the single-lined orbit we derived for β CMi (f (M ) = 2.0 × 10 −3 M ⊙ ) is indicative of a very low mass companion, similar to the aforementioned Be binaries with ultraviolet detections of the companions.…”
Section: Discussionmentioning
confidence: 96%
“…Similar direct ultraviolet detections of hot subdwarf companions have been accomplished for FY CMa (Peters et al 2008), 59 Cyg (Peters et al 2013), HR 2142 (Peters et al 2016), and o Pup (Rivinius et al 2012, Koubský et al 2012) all with small mass functions in the range of 2 × 10 −3 − 1.3 × 10 −2 M ⊙ . Other Be binaries that have not had direct detections of the companion stars such as γ Cas (Smith et al 2012) or ζ Tau (Ruždjak et al 2009) also show similar mass functions (f (M ) = 1 × 10 −3 and f (M ) = 6 × 10 −3 respectively) that indicate low-mass companions. The mass function of the single-lined orbit we derived for β CMi (f (M ) = 2.0 × 10 −3 M ⊙ ) is indicative of a very low mass companion, similar to the aforementioned Be binaries with ultraviolet detections of the companions.…”
Section: Discussionmentioning
confidence: 96%
“…unsaturated profiles. The reasons the emission wings should provide a good estimate of the true orbital motion of the Be primary around the common centre of gravity with the secondary were recently summarized in detail by Ruždjak et al (2009). To them, we can add that Poeckert & Marlborough (1978) modelled the Hα emission of γ Cas, and their model showed that the Hα emission wings originate in regions that are much closer to the star than the radiation that is forming the upper part of the line.…”
Section: Long-term and Periodic Rv Changes And The New Orbital Solutionsmentioning
confidence: 97%
“…2. For binary Be stars with strong Hα emission, this is the best measure of the true orbital motion of the Be component -see Božić et al (1995), Ruždjak et al (2009) and Peters et al (2013). This is not so for BR CMi, since its Hα emission rises to only 20% above the continuum level, and the measured RV curve of the Hα emission wings is poorly defined and has a phase shift with respect to expected orbital motion of component 1.…”
Section: Finding Reliable Orbital Elementsmentioning
confidence: 99%